Remedial Effects of Motivational Incentive on Declining Cognitive Control In Healthy Aging and Parkinson's Disease - Harsay, Helga A.; Buitenweg, Jessika I.; Wijnen, Jasper G.; Guerreiro, Maria J.; Ridderinkhof, K. Richard (Frontiers in Aging Neuroscience, 2010)
The prospect of reward may provide a motivational incentive for optimizing goal-directed behavior. Animal work demonstrates that reward-processing networks and oculomotor-control networks in the brain are connected through the dorsal striatum, and that reward anticipation can improve oculomotor control via this nexus. Due perhaps to deterioration in dopaminergic striatal circuitry, goal-directed oculomotor control is subject to decline in healthy seniors, and even more in individuals with Parkinson's disease (PD). Here we examine whether healthy seniors and PD patients are able to utilize reward prospects to improve their impaired antisaccade performance. Results confirmed that oculomotor control declined in PD patients compared to healthy seniors, and in healthy seniors compared to young adults. However, the motivational incentive of reward expectation resulted in benefits in antisaccade performance in all groups alike. These findings speak against structural and nonmodifiable decline in cognitive control functions, and emphasize the remedial potential of motivational incentive mechanisms in healthy as well as pathological aging.